Comparative study of Diffserv schedulers : Round Robin & Weighted Interleaved Round Robin - Norazuana Abu Bakar (2023)
This project is to carry out a comparative study of Diffserv schedulers. In Diffserv, there are four types of schedulers that are usually used to schedule the packets in the network; Weighted Round Robin, Weighted Interleaved Round Robin, Round Robin and Priority Queue. This comparative study is based on Round Robin and Weighted Interleaved Round Robin and the parameters that are being studied are queue size and queue loss. A simulation study was conducted using these two scheduling techniques. By looking at these parameters, the effectiveness of Quality of Service (QoS) provided by different scheduling techniques are studied.